Factors influencing hospital anxiety and depression among emergency department nurses during the COVID-19 pandemic: A multi-center cross-sectional study - Alzahrani, Naif S.; Almarwani, Abdulaziz Mofdy; Asiri, Saeed A.; Alharbi, Hanan F.; Alhowaymel, Fahad M. (Frontiers in Psychiatry, 2022)
Abstract Introduction: The emergency department (ED) is a highly stressful environment, which exposes nurses to infection. ED nurses handle life-threatening conditions, endure long working hours, and deal with anxious patients and their families. Aim: This study aimed to examine factors, which may influence anxiety and depression levels among emergency department nurses during the COVID-19 pandemic. Methods: A cross-sectional design was used with 251 participants from six hospitals in Saudi Arabia (mean age = 32.7 ± 6.59, range = 21–54 years, 70.5% females). Data were collected using the Hospital Anxiety and Depression Scale (HADS), and the analysis was conducted using Structural Equation Modeling (SEM). Results: Based on the HADS scores, 29.1% and 25.5% of ED nurses were identified as doubtful cases for depression and anxiety, respectively. Additionally, 34.7% and 43.3% of ED nurses were identified as definite cases for depression and anxiety, respectively. Higher anxiety levels were observed among female nurses, nurses with lower physical activity levels, and nurses who worked in urban areas. Low physical activity levels and more than six years of work experience correlated with a higher level of depression. None of the hypothesized paths in the anxiety and depression models were significant, except for two observed variables—namely, work location and physical exercise in the anxiety model and physical exercise in the depression model. Conclusion: Emergency department nurses expressed high levels of anxiety and depression during the COVID-19 pandemic, which may negatively affect their performance and reduce care quality. Therefore, health care leaders should implement specialized mental health education programs focused on nursing occupational safety and support to improve emergency department nurses’ psychological well-being. Specific attention should be paid to ED female nurses who work in urban areas, especially those with more than six years of experience.